Ibn Mujahid's Canonical Legacy: Examining Sanad Authentication and Political Factors in the Standardization of Qirā’āt Sab’ah - Afrida Arinal Muna; Munirul Ikhwan (UIN Sunan Kalijaga Yogyakarta, 2023)
This research delves into the study of qirā’āt, specifically examining variations in Qur'anic recitation within the modern context of Qur'anic studies. Academic literature has typically overlooked qirā’āt, tending to emphasize linguistic aspects of qira'at in general. However, recent scholarly discussions underscore the increasing significance of scrutinizing the authenticity of qirā’āt. The presence of uncertainties and disputes concerning the authenticity of qirā’āt, both within Western and Muslim scholarly circles, renders this subject exceptionally intriguing for investigation. Drawing upon Michel Foucault's theory of the archaeology of knowledge and Shahab Ahmad, this study endeavors to bridge the existing knowledge gap by tracing the historical development of the standardization and canonization of qirā’āt. Specifically, our research will shed light on the motivations and procedures employed by Ibn Mujahid in designating seven Imams as authoritative figures in the canonization of qirā’āt sab’ah. Furthermore, we strived to uncover the ways in which political factors exerted influence over the endeavor to 'canonize' qirā’āt in seven distinct variants. Our findings ultimately reveal that the success of Ibn Mujahid's codification and canonization of qirā’āt hinged not solely on the narrative of unifying Muslim perspectives on the diverse recitation variants but was also significantly shaped by underlying political considerations throughout the process. These discoveries offer fresh insights into comprehending the historical dynamics of qirā’āt al-Qur'an and underscore the crucial importance of considering the political backdrop in understanding religious traditions.